Application of technology acceptance model (TAM) through the concept of Perceived Usefulness in the BRIguna Digital marketing program - Sonia Anuar Sonia; Endy Gunanto Marsasi (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
Researchers examined a company engaged in banking that generally provides service products where this company does several services to market its products. This study aims to evaluate the services provided through marketing media companies use in Mobile Banking, namely BRIguna Digital, to make it easier for product users to carry out activities online. This study used descriptive qualitative research methods and data collection through observation, in-depth interviews, company secondary data, and documentation collection. This research evaluates marketing services used through the BRIMO application to facilitate the systems and services provided to customers to minimize the failure of online transactions so that BRIMO users are increasingly spreading, especially in the BRIguna Digital program, which is not widely known. This evaluation is carried out to improve the existing system and introduce BRIMO, especially in the digital BRIguna program, so that it is better known and has many users. The evaluation of this program uses the theory of the Technology Acceptance Model with the concept of Perceived Usefulness which will be implemented to support the PT. Bank Rakyat Indonesia in evaluating the BRIguna Digital program